Perspectivas do Encontro Casal Grávido em um Hospital Amigo da Criança de Belo Horizonte/MG - Cintia Ribeiro Santos (2020)
SANTOS, Cintia Ribeiro. Perspectives of the Casal Grávido Meeting in a Baby Friendly Hospital in Belo Horizonte/MG. 2020. 114 f. Dissertation (Professional Master in Health Services Management) - School of Nursing, Federal University of Minas Gerais, Belo Horizonte, 2020. Introduction: This dissertation it deals with the actions of the Casal Grávido Meeting, an educational health practice for pregnant women and their social support network at a Baby Friendly Hospital in Belo Horizonte / MG. Objective: To understand the importance of the Pregnant Couple Meeting in relation to the preparation for labor, birth and breastfeeding. Method: To achieve the proposed objective, a qualitative approach was chosen and the case study was used as the means of investigation, whose sample universe was the women and their companions of choice who participated in the Casal Grávido Meeting. The sample consisted of 15 women and their respective 15 companions, totaling 30 interviewees, chosen by the convenience sampling technique. Data were collected through semi-structured interviews, conducted by a research assistant in each interview, in order to avoid conflicts of interest and to minimize the risk of bias. For the analysis and interpretation of the data, the content analysis technique proposed by Bardin was used. The MAXQDA software was used for the analysis of qualitative data and mixed research methods, which enabled a broad qualitative analysis. The thematic categories were anchored in the theoretical framework of the research. The grouping of themes emerged according to the answers to each question asked in the interviews. Results: It became possible to identify, through the reports of the participating couples, how the actions of the Meeting contributed positively to the experience during labor, birth and breastfeeding. It was also identified that the basic theoretical elements of the Meeting's practices are aligned with the guidelines for patient safety in obstetrics, as well as in other public policies that recommend good practices for the time of delivery, birth and breastfeeding. Conclusion: the relevance of the Casal Grávido Encounter for the prevention of diseases and injuries during pregnancy became evident, as well as to expand the knowledge of pregnant women and their companions of choice about baby care after delivery, especially in relation to breastfeeding maternal. Dissertation product: Based on the results obtained, a course plan for the training of HSF obstetric nurses and other professionals interested in good practices in childbirth, birth and breastfeeding is presented as a technical product.